Outcomes of the "STEPS" HIV prevention training program for young males in the penitentiary institution, Ukraine. Issue 2 (11th June 2018) - Dauria, Emily; Tolou-Shams, Marina; Skipalska, Halyna; Bachmaha, Mariya; Hodgdon, Sara
Abstract : Purpose: Ukraine has one of the fastest growing HIV epidemics globally. Due to their engagement in high-risk behaviors, adolescents and emerging adults involved with the penitentiary system are at a particularly high risk of HIV-acquisition. To address the epidemic, young males (aged 14 to 20 years) in penitentiary institutions across Ukraine participated in a ten-week, group-based HIV-prevention intervention (STEPS). The paper aims to discuss these issues. Design/methodology/approach: The authors analyzed clinical and programmatic services data collected as part of an evaluation of the STEPS intervention. Paired t -tests and χ 2 were used to examine pre- and post-intervention differences in HV knowledge, attitudes, and risk behaviors and alcohol and other drug use knowledge. Findings: In total, 105 male youths participated in the ten-session STEPS intervention. At baseline, males reported high frequencies of risk behaviors (e.g. unprotected sexual activity, injection drug use), moderate levels of HIV-related knowledge, and negative attitudes toward HIV and people living with HIV. At follow-up (immediately following the last STEPS session), participants' HIV-related knowledge substantially improved and participants tended to have more favorable attitudes toward HIV. Research limitations/implications: Outcomes suggest that knowledge and attitudes about HIV among Ukrainian incarcerated youth can improve as a result of group-based HIV-prevention intervention. Originality/value: In Ukraine, individuals involved with the criminal justice system are one of the populations most-at-risk for HIV; criminal justice-involved adolescents and young adults are disproportionately affected by the HIV epidemic. Research among this sub-population is limited. This study aims to address this gap by evaluating an on-going group-based HIV-prevention program designed to reduce adolescent risk of HIV.